In vitro cytotoxic and antiproliferative effects of portulaca oleracea methanol extract on breast, cervical, colon and nasopharyngeal cancerous cell lines - Gek, Choo Sarah Tan; Kar, Mun Wong; Gui, Qi Pearle-Wong; Siau, Li Yeo; Swee, Keong Yeap; Beow, Chin Yiap; Hueh, Zan Chong (Universiti Kebangsaan Malaysia, 2013)
Portulaca oleracea is a ubiquitous garden weed that has been traditionally used as antidiabetic and anti-inflammation agent. However, the potential anti-proliferative and cytotoxic effects of Portulaca oleracea towards cancerous cells are still unclear. Human hormone dependent breast cancer MCF-7 cell, colon cancer HT-29, cervical cancer Hela cell and nasopharyngeal cancer CNE-1 cell were used in this study. P. oleracea was extracted using methanol and the cytotoxicity against various cancerous cell lines was evaluated using 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide solution (MTT) assay. The antiproliferation effect and cell cycle arrest were assessed using BrdU proliferation assay and flow cytometry cell cycle RNase/PI analysis, respectively. Portulaca oleracea methanol extract was able to reduce viability of all the tested cancerous cell lines. However, IC50 was only observed in CNE-1 cell (92 μg/mL). BrdU incorporation assay indicated anti-proliferation of Portulaca oleracea treated MCF-7 cells in a dose-dependent manner. A significant increase in the sub G0/G1cell population phase observed by cell cycle analysis indicates the occurrence of apoptotic events. In conclusion, Portulaca oleracea showed anti-proliferative effect on CNE-1, HeLa and HT-29 and DNA fragmentation on MCF-7 cells.